Fekete-Szego inequality for certain class of close-to-convex functions on a real parameter / Nonis Airina Mohd Arshad - Mohd Arshad, Nonis Airina (Universiti Teknologi MARA, Negeri Sembilan, 2024)
In the present paper, we examine the upper bounds of the second Fekete-Szego inequality. The geometric function theory of complex analysis is a fascinating study area, focusing on analytic univalent functions and their geometric properties. However, this field faces significant challenges due to its complexity, involving complex mathematical concepts, proofs, and abstract logic. Researchers often struggle to select suitable methods for mathematical analysis. Coefficient inequalities are a popular topic in this field, allowing researchers to quantify and understand coefficient behavior in function power series expansions.